Traditional Chinese medicine for treating aplastic anemia - Jing Guan; YiHui Zhao; Ting Wang; Rong Fu (Frontiers Media S.A., 2023)
Aplastic anemia (AA) is a bone marrow failure disease caused by T cell hyperfunction. Although the overall response rate has been improved by immunosuppressive therapy (IST) plus Eltrombopag, 30% of patients have either no response or relapse. We therefore attempted to find other ways to improve the outcomes of AA patients. Traditional Chinese medicine has the advantages of low cost, reasonable effects, and few side effects. More and more clinical studies have confirmed that traditional Chinese medicine has a beneficial role in treating AA patients. This article reviews the potential mechanism of traditional Chinese medicine or its active ingredients in the treatment of AA. These include improving the bone marrow microenvironment, regulating immunity, and affecting the fate of hematopoietic stem cells. This provides useful information for further treatment of AA with integration of traditional Chinese and Western medicine and the development of new treatment strategies.